Recycling method for preparing 3D printing powder consumables from waste wind power blades

By modifying the glass fibers of waste wind power blades into microspheres and mixing them with nylon powder, it is prepared into 3D-printed powder consumables, which solves the problem of recycling and resource utilization of waste wind power blades and achieves efficient and economical resource utilization.

CN119752162APending Publication Date: 2025-04-04ZHANGJIAKOU JIANTOU NEW ENERGY CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510022274.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively recycle and resource utilization of waste wind power blades, resulting in the problems of environmental pollution and low economic value in their disposal methods.

Method used

Through physical crushing-pyrolysis, fine grinding and sol gel, the glass fibers of the waste wind power blades are modified into glass fiber microspheres and mixed with nylon powder to prepare into 3D printed powder consumables.

Benefits of technology

It realizes efficient recycling and resource utilization of waste wind power blades, and the prepared 3D printed powder consumables have better performance and have broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752162A_ABST
    Figure CN119752162A_ABST
Patent Text Reader

Abstract

The invention discloses a method for recycling 3D printing powder consumables prepared from waste wind power blades, which comprises the following steps: physically crushing and pyrolyzing the waste wind power blades to obtain pure glass fibers, finely grinding and cutting the glass fibers into short glass fibers, preparing glass fiber microspheres by adopting a sol-gel method, and preparing the 3D printing powder consumables from the waste wind power blades. The glass fiber microspheres and the nylon material are mixed to prepare the glass fiber-nylon mixed 3D printing powder consumable, and the obtained 3D printing powder consumable has excellent performance. The requirements of the 3D printing technology in the future are continuously increased, the waste wind power blade recycling technology is combined, high-economic-value resource utilization of the waste blades is achieved, and wide application prospects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of recycling waste wind turbine blades, and specifically relates to a method for recycling waste wind turbine blades for preparing 3D printing powder consumables. Background Art

[0002] Global development shows a trend of low carbon, green, environmental protection and energy conservation, striving to achieve the expected "carbon peak and carbon neutrality". Wind energy is a clean and renewable energy source. At the beginning of this century, a large number of wind power stations were built, and the growth rate is accelerating. The design life of a wind power station is generally about 20 years. At present, a large number of wind turbines in use are facing scrapping, and the number is increasing year by year. The blades of wind turbines are thin shell structures, and composite fiber materials generally account for more than 90% of the entire wind turbine blades. According to data, the consumption of composite fiber materials in China's wind turbine blade industry exceeded 20,000 tons in 2019. Some experts predict that the global discarded wind turbine blades will reach more than 225,000 tons by 2034.

[0003] At present, the traditional disposal methods of discarded wind turbine blades are: open-air stacking, landfill or incineration. Open-air stacking and landfilling occupy a large area, are difficult to degrade, and will release some toxic substances, which will further pollute the soil and groundwater system; direct incineration will produce a large amount of toxic gases and smoke.

[0004] At present, the main recycling technologies for discarded blades are: mechanical recycling, thermal recycling and chemical recycling. Among them, mechanical recycling is a method of secondary utilization of crushed composite materials as raw materials. For large composite materials such as wind turbine blades, their volume is large and they must be pre-cut before crushing. This recycling technology has low cost and simple process, and is widely used in the recycling of fiber-reinforced polymer composites. However, most of the recycled products obtained by this method are of low value, and the fibers are severely damaged during the recycling process, and long fibers cannot be obtained. The chemical recycling method uses chemical reagents to convert the resin matrix of the composite material into small molecules, thereby recovering glass fibers. Chemical recycling is a method of using chemical modification or pyrolysis to make waste into other recyclable materials. This recycling method is usually difficult and costly.

[0005] The fiber materials in wind turbine blades can be used as resources, specifically in the following ways: 1. Application in concrete: Concrete is the most widely used building material, and its main components are cement and fine and coarse sand and gravel aggregates. The global consumption of sand and gravel aggregates exceeds 17.5 billion tons per year. Its mining not only releases a large amount of cobalt, but also damages mountains and riverbeds. The tensile, compressive and shear strengths of wind turbine blade glass fiber reinforced plastic (FRP) materials can reach 600MPa, 500MPa and 125MPa respectively, and its good mechanical properties basically meet the characteristics of concrete aggregates. Therefore, the use of waste wind turbine blade FRP materials to replace natural concrete aggregates can prepare green and low-carbon concrete, alleviate the consumption and damage to resources and the environment, and have good economic and environmental benefits. 2. Application in cement mortar: The coordinated disposal of waste wind turbine blades in cement kilns is a relatively mature resource technology currently in use. It belongs to calorific value recovery, and at the same time utilizes the glass fiber materials in the blades, which better realizes the resource utilization of waste blades. The blades were crushed into 30 mm particles using a single-shaft crusher, and calcined at 850°C, indicating that the organic matter in the blade fragments can be burned within 2 minutes. 3. Application in geopolymers: Geopolymers are a new type of green and recyclable aluminosilicate cementitious material, which is formed by reactions such as "dissolution-reconstruction-condensation". In the production process, the carbon content is reduced by more than 90% compared with silicate cement, so it is often used as a substitute for silicate cement. In addition, geopolymers can be synthesized using various types of industrial solid wastes rich in silicon and aluminum, such as fly ash, blast furnace slag, and red mud, as a matrix, providing an effective way to recycle industrial solid wastes. [6] The FRP material of discarded wind turbine blades has excellent mechanical properties and plays a good role in enhancing the strength of geopolymers.

[0006] However, the above resource utilization methods mostly use waste wind turbine blades for building materials, which have poor economic value. In addition, the mixing ratio of FRP materials of waste wind turbine blades should not be too high to ensure the better strength of building materials. Therefore, developing a waste blade recycling method with high economic value is of great significance to realize its resource utilization. Summary of the invention

[0007] The present invention provides a recycling method for preparing 3D printing powder consumables from discarded wind turbine blades. The discarded wind turbine blades are crushed and impurities are removed to obtain pure micron-level glass fibers. At the same time, the strip-shaped long glass fibers are modified into glass fiber microspheres, which are used as 3D printing powder consumables, thereby overcoming the technical difficulties of using discarded wind turbine blades to prepare 3D printing powder consumables.

[0008] The above technical problems of the present invention are mainly solved by the following technical solutions.

[0009] A method for recycling waste wind turbine blades to prepare 3D printing powder consumables, comprising the following steps:

[0010] S1 Physical crushing-pyrolysis: Remove the metal parts of the discarded wind turbine blades, cut them with a cutting machine, and then crush them with a shredder; then pyrolyze the crushed wind turbine blades under anaerobic or anoxic conditions to obtain pure glass fibers;

[0011] S2 fine grinding: grinding the pure glass fiber to obtain micron-sized short glass fibers;

[0012] S3 sol-gel: short glass fibers are added to a sodium polyacrylate (PAANa) solution, and the pH value is adjusted to 2.8-3.2 to obtain a mixed solution, and a solution containing gold ions is evenly dropped into the mixed solution and stirred in a water bath, and glass fiber microspheres are obtained by filtration; wherein the gold ions catalyze the decomposition of PAANa to form polyacrylic acid (PAA) gel, which is coated on the surface of the short glass fibers to form cores, and the PAA gel coated on the short glass fibers continues to grow and form glass fiber microspheres;

[0013] S4 uniform mixing: glass fiber microspheres are mixed with nylon powder, and ground evenly to obtain glass fiber-nylon mixed 3D printing powder consumables (glass fiber nylon mixed powder).

[0014] Furthermore, the particle size after being cut by the cutting machine in step S1 is 50mm-100mm.

[0015] Furthermore, the particle size after pulverization by the shredder in step S1 is 50 μm-10 mm.

[0016] Furthermore, the shredder in step S1 adopts a rotating diamond rotary knife micronization processing device.

[0017] Furthermore, the pyrolysis in step S1 decomposes impurities (balsa wood, resin, etc.) in the blade into small molecular organic polymers, which are discharged along with the pyrolysis gas, thereby obtaining pure glass fibers.

[0018] Furthermore, in step S1, the pyrolysis temperature is 500-600° C., and the pyrolysis time is 3-4 hours.

[0019] Furthermore, the grinding time in step S2 is 1-2h.

[0020] Furthermore, step S2 also includes filtering the ground glass fiber using an electric vibrating screen. Furthermore, the electric vibrating screen has a mesh size of 1800 or more.

[0021] Furthermore, in step S2, the particle size of the short glass fibers is less than 50 μm.

[0022] Furthermore, in step S3, sulfuric acid and ammonia water are used to adjust the pH value.

[0023] Furthermore, in step S3, a syringe pump is used to evenly drip the solution containing gold ions into the mixed solution.

[0024] Furthermore, the molecular weight of the sodium polyacrylate in step S3 is 10 5 -10 6 .

[0025] Furthermore, the initial concentration of the sodium polyacrylate solution in step S3 is 1%-5%.

[0026] Furthermore, the amount of short glass fibers added to the mixed solution in step S3 is 10wt%-20wt%.

[0027] Furthermore, the solution containing gold ions in step S3 is a chloroauric acid solution with a concentration of 0.1-0.5 mmol / L and a pH value of 2.8-3.2.

[0028] Furthermore, in step S3, the volume ratio of the solution containing gold ions to the mixed solution is 1:50-100.

[0029] Furthermore, in step S3, the water bath temperature is 60°C-80°C.

[0030] Furthermore, the stirring time in step S3 is 2-4 hours.

[0031] Furthermore, the mass percentage of the glass fiber microsphere powder in step S4 is 20wt%-40wt%.

[0032] Furthermore, the particle size of the 3D printing powder consumables after uniform grinding is less than 50 μm.

[0033] Compared with the prior art, the present invention has the following advantages:

[0034] Glass fiber microspheres are obtained by recycling and modifying the glass fibers in discarded wind turbine blades, and then mixed with nylon materials to form 3D printing powder consumables. Specifically, through grinding, sol-gel and other steps, the strip-shaped long glass fibers of discarded wind turbine blades are modified into glass fiber microspheres. The 3D printing powder consumables prepared therefrom have better performance than the powder consumables prepared without modification. The demand for 3D printing technology will continue to increase in the future. The present invention combines the waste wind turbine blade recycling technology to realize the high economic value resource utilization of waste blades, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Flowchart for preparing 3D printing powder consumables for discarded wind turbine blades.

[0036] Figure 2 SEM image of pure glass fiber after physical crushing and pyrolysis.

[0037] Figure 3 This is the SEM image of glass fiber spheres. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further specifically described below through embodiments and comparative examples.

[0039] Example 1

[0040] like Figure 1 As shown, a method for recycling waste wind turbine blades to prepare 3D printing powder consumables includes the following steps:

[0041] (1) Physical crushing-pyrolysis: Remove the metal parts of the discarded wind turbine blades, cut them with a cutting machine to a particle size of 50mm-100mm, and then crush them with a shredder to a particle size of 50μm-10mm. Then, pyrolyze the crushed wind turbine blades under anaerobic conditions to obtain pure glass fiber. The shredder uses a rotating diamond rotary knife micronization treatment device. The pyrolysis temperature is 600℃ and the pyrolysis time is 3h. The SEM image of the pure glass fiber is shown in Figure 2 , glass fiber strips can be observed.

[0042] (2) Fine grinding: The obtained pure glass fiber is carefully ground in a mortar for 2 hours, and filtered through an electric vibrating screen to obtain micron-grade (less than 50 μm) short glass fibers, wherein the mesh of the electric vibrating screen is 1800 mesh or more.

[0043] (3) Sol-gel: The ground short fibers were added to a 10 6 In a sodium polyacrylate (PAANa) solution, the initial concentration of the PAANa solution is 1%, and the amount of short glass fiber added is 10wt%. The pH value is adjusted to 3 using sulfuric acid and ammonia water to obtain a mixed solution. The solution containing gold ions is evenly dripped into the mixed solution using a syringe pump and stirred in a water bath at 80°C for 3 hours. After the solution is cooled, it is filtered to obtain spherical particles, that is, glass fiber microspheres. The solution of gold ions is a chloroauric acid solution with a concentration of 0.5mmol / L and a pH value of 3; the volume ratio of the solution containing gold ions to the mixed solution is 1:100. Gold ions catalyze the decomposition of PAANa to form polyacrylic acid (PAA) gel, which is coated on the surface of the short glass fiber to form a core. The PAA gel coated with the glass fiber continues to grow and form glass fiber microspheres.

[0044] (4) Morphology test: SEM image of glass fiber microspheres is shown in Figure 3 , evenly distributed glass fiber microspheres can be observed.

[0045] (5) Uniform mixing: The glass fiber microsphere A powder and the nylon powder were uniformly mixed at a mass ratio of 2:8, 3:7, and 4:6, respectively. After uniform grinding, glass fiber-nylon mixed 3D printing powder consumables were prepared, which were recorded as glass fiber microsphere nylon mixed powders A, B, and C.

[0046] (6) Performance testing: The glass fiber nylon mixed powders prepared with different mixing ratios were subjected to standardized tests, including whether the appearance quality, chemical composition (in accordance with GB / T 11170), particle size and particle size distribution (in accordance with GB / T1480), fluidity (in accordance with GB / T 1482), bulk density (in accordance with GB / T 1479.1), and tap density (in accordance with GB / T 5162) meet the national standards. The glass fiber nylon mixed powders prepared with different mixing ratios were printed into the same model to compare the quality parameters of the model, such as tensile strength (test method GB / T 1040), flexural strength (test method GB / T 9341), dimensional accuracy (test method GB / T 14486), and surface finish (test method GB / T 14234).

[0047] The 3D printing powder has an off-white appearance, a particle size of 20μm-50μm, a fluidity of 31s / 50g-35.0s / 50g, and a bulk density of 2.13g / cm 3 -2.30g / cm 3 , tap density is 2.45g / cm 3 -2.50g / cm 3 .

[0048] The tensile strength of the 3D printed model is 80Mpa-86 Mpa, the bending strength is 135Mpa-150 Mpa, the dimensional accuracy is ±0.3mm-0.4mm, and the average surface roughness (reflecting the surface finish parameter) is 300μm-500μm.

[0049] Comparative Example 1

[0050] This comparative example is used to evaluate the impact of key steps in the modification process on the effects of the prepared 3D printing powder consumables.

[0051] The preparation method of glass fiber balls is the same as that of Example 1, but without dropping the gold ion solution. The obtained glass fiber ball powder (unevenly distributed) and nylon powder are uniformly mixed at a mass ratio of 3:7, and the glass fiber microsphere nylon mixed powder D is prepared after uniform grinding.

[0052] The specific test data are as follows:

[0053]

[0054] It is obvious that the 3D printing powder consumables prepared by modifying the glass fiber microspheres by adding the key step of gold ion solution have better performance.

[0055] Comparative Example 2

[0056] This comparative example is used to evaluate the effects of 3D printing powder consumables prepared from modified glass fiber microspheres and unmodified strip-shaped long glass fibers.

[0057] The pure glass fiber (long glass fiber strip) obtained in step (1) is uniformly mixed with nylon powder in a ratio of 3:7, and then uniformly ground to prepare a long glass fiber strip nylon mixed powder E.

[0058] The specific test data are as follows:

[0059]

[0060] It is obvious that the 3D printing powder consumables prepared by glass fiber microspheres modified by sol-gel and other steps have better performance than the 3D printing powder consumables prepared by unmodified long glass fiber strips, and have more application prospects.

[0061] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A method for recycling waste wind turbine blades to prepare 3D printing powder consumables, characterized by: The steps include: S1 Physical crushing-pyrolysis: Remove the metal parts of the discarded wind turbine blades, cut them with a cutting machine, and then crush them with a shredder; then pyrolyze the crushed wind turbine blades under anaerobic or anoxic conditions to obtain pure glass fibers; S2 fine grinding: grinding the pure glass fiber to obtain micron-sized short glass fibers; S3 sol-gel: short glass fibers are added to a sodium polyacrylate solution, the pH value is adjusted to 2.8-3.2 to obtain a mixed solution, a solution containing gold ions is evenly dropped into the mixed solution and stirred in a water bath, and glass fiber microspheres are obtained by filtration; S4 uniform mixing: Mix the glass fiber microspheres with the nylon powder and grind them evenly to obtain the glass fiber-nylon mixed 3D printing powder consumables.

2. The method for recycling waste wind turbine blades for preparing 3D printing powder consumables according to claim 1, characterized in that: The particle size after being cut by the cutting machine in step S1 is 50mm-100mm; the particle size after being crushed by the shredder is 50μm-10mm.

3. The method for recycling waste wind turbine blades for preparing 3D printing powder consumables according to claim 1, characterized in that: The pyrolysis temperature in step S1 is 500-600° C., and the pyrolysis time is 3-4 hours.

4. The method for recycling waste wind turbine blades for preparing 3D printing powder consumables according to claim 1, characterized in that: The grinding time in step S2 is 1-2h.

5. The method for recycling waste wind turbine blades for preparing 3D printing powder consumables according to claim 1, characterized in that: Step S2 also includes filtering the ground glass fiber using an electric vibrating screen; and / or, The particle size of the short glass fibers in step S2 is less than 50 μm.

6. The method for recycling waste wind turbine blades for preparing 3D printing powder consumables according to claim 1, characterized in that: In step S3, sulfuric acid and ammonia water are used to adjust the pH value; and / or, In step S3, a syringe pump is used to evenly drop the solution containing gold ions into the mixed solution.

7. The method for recycling waste wind turbine blades for preparing 3D printing powder consumables according to claim 1, characterized in that: The molecular weight of the sodium polyacrylate in step S3 is 10 5 -10 6 , the initial concentration is 1%-5%; and / or, The amount of short glass fibers added to the mixed solution in step S3 is 10wt%-20wt%.

8. The method for recycling waste wind turbine blades for preparing 3D printing powder consumables according to claim 1, characterized in that: The solution containing gold ions in step S3 is a chloroauric acid solution with a concentration of 0.1-0.5 mmol / L and a pH value of 2.8-3.

2.

9. The method for recycling waste wind turbine blades for preparing 3D printing powder consumables according to claim 1, characterized in that: In step S3, the water bath temperature is 60° C.-80° C.; the stirring time is 2-4 h.

10. The method for recycling waste wind turbine blades for preparing 3D printing powder consumables according to claim 1, characterized in that: The mass percentage of the glass fiber microspheres in step S4 is 20wt%-40wt%; and / or, After being evenly ground in step S4, the particle size of the 3D printing powder consumables is less than 50 μm.

Citation Information

Cited By

  • Composite catalyst for recovering monophenol from waste fan blades as well as preparation method and application of composite catalyst

    CN120900697A